The Inflammatory Mechanism of Parkinson’s Disease: Gut Microbiota Metabolites Affect the Development of the Disease Through the Gut–Brain Axis - Ai Gao; Jiaqi Lv; Yanwei Su (Brain Sciences)
Parkinson’s disease is recognized as the second most prevalent neurodegenerative disorder globally, with its incidence rate projected to increase alongside ongoing population growth. However, the precise etiology of Parkinson’s disease remains elusive. This article explores the inflammatory mechanisms linking gut microbiota to Parkinson’s disease, emphasizing alterations in gut microbiota and their metabolites that influence the disease’s progression through the bidirectional transmission of inflammatory signals along the gut–brain axis. Building on this mechanistic framework, this article further discusses research methodologies and treatment strategies focused on gut microbiota metabolites, including metabolomics detection techniques, animal model investigations, and therapeutic approaches such as dietary interventions, probiotic treatments, and fecal transplantation. Ultimately, this article aims to elucidate the relationship between gut microbiota metabolites and the inflammatory mechanisms underlying Parkinson’s disease, thereby paving the way for novel avenues in the research and treatment of this condition.